Dragons : fearsome monsters from myth and fiction (New York : Amber Books : Scholastic, 2013)
Features ancient legends, mythological dragons, and media dragons, all illustrated with stunning artwork.
Includes index.
1000
Keywords: Dragons -- Folklore; Folklore